Unraveling the Threads: A Comprehensive Exploration of the Interplay be-tween Social Isolation and Academic Stress Among Students - Walsham, Walsham; Perlman , Tancredi Thorne; Sihotang, Demita (Institute for Law and Economics Studies, 2023)
In the labyrinthine landscape of student experiences, this research endeavors to unravel the intricate relationship between social isolation and academic stress. Utilizing a mixed-methods approach, our study amalgamates quantitative rigor with qualitative depth to paint a comprehensive portrait of the challenges faced by students navigating the confluence of social dynamics and educational pressures. The primary objective is to understand how social isolation influences the prevalence and intensity of academic stress among students. Through a dual lens of theory and practice, the research aims to contribute to both the theoretical frameworks shaping stress models and the practical interventions implemented within educational institutions. A diverse sample of students across various educational institutions participated in this study. Quantitative data were gathered through structured surveys, probing the prevalence of social isolation and its correlation with academic stress. Qualitative insights were obtained through in-depth interviews and focus group discussions, unraveling the nuanced experiences and coping mechanisms employed by students. The research affirms a significant positive correlation between social isolation and academic stress, establishing a quantifiable connection. Qualitative narratives unveil the emotional dimensions of social isolation, emphasizing loneliness, fear of failure, and a sense of disconnection as prevalent themes. Stressors such as performance expectations and a competitive academic environment emerge as catalysts that intensify stress levels among socially isolated students. Theoretical implications extend to the refinement of stress models by integrating emotional well-being and recognizing intersectionality. Practical implications advocate for tailored institutional support systems, mental health literacy initiatives, and the integration of social support into academic programs. Collaborative efforts between researchers and practitioners are essential to bridge the gap between theory and practice. As this research concludes, it beckons educators, institutions, and policymakers to heed the call for transformative change. By prioritizing the emotional and social well-being of students alongside academic success, we pave the way for educational environments that foster resilience, support, and holistic growth. This research stands as a catalyst for ongoing conversations and actions, recognizing that the journey to understanding and enhancing student experiences is an ever-evolving endeavor